2011
DOI: 10.1183/09031936.00042111
|View full text |Cite
|
Sign up to set email alerts
|

Sputum colour and bacteria in chronic bronchitis exacerbations: a pooled analysis

Abstract: We examined the correlation between sputum colour and the presence of potentially pathogenic bacteria in acute exacerbations of chronic bronchitis (AECBs).Data were pooled from six multicentre studies comparing moxifloxacin with other antimicrobials in patients with an AECB. Sputum was collected before antimicrobial therapy, and bacteria were identified by culture and Gram staining. Association between sputum colour and bacteria was determined using logistic regression.Of 4,089 sputum samples, a colour was rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
0
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 32 publications
2
55
0
13
Order By: Relevance
“…In prospective studies, mucoid sputum is usually described as colourless white, and purulence as ranging from pale yellow to dark green. A recently pooled analysis of clinical trials results in acute exacerbations of chronic bronchitis showed sputum colour to be a stronger predictor of pathogenic microorganism presence than other factors, including sputum purulence [5]. The authors found a significant and consistent relationship between purulence and the presence of a pathogenic bacteria in sputum, although it had less predictive value that the colour of the sample.…”
Section: From the Authorsmentioning
confidence: 58%
“…In prospective studies, mucoid sputum is usually described as colourless white, and purulence as ranging from pale yellow to dark green. A recently pooled analysis of clinical trials results in acute exacerbations of chronic bronchitis showed sputum colour to be a stronger predictor of pathogenic microorganism presence than other factors, including sputum purulence [5]. The authors found a significant and consistent relationship between purulence and the presence of a pathogenic bacteria in sputum, although it had less predictive value that the colour of the sample.…”
Section: From the Authorsmentioning
confidence: 58%
“…This group demonstrates identical findings to our main cohort: that C-reactive protein (CRP) levels and body temperature are strongly associated with viral detection (either alone or with bacteria) but not with bacterial detection alone, and suggests that the findings in the main cohort are not due to a lack of sputum samples. We would also like to point out that it is similarly impossible to detect viruses if one does not test for them and of the studies referenced by M. Miravitlles and C. Llor as demonstrating an association between CRP level, sputum purulence and bacterial detection [1][2][3][4][5], none has tested for respiratory viruses apart from that by DANIELS et al [5] and this was not in a standard manner. Interestingly, another study referenced by the authors [6] did systematically test patients with exacerbations for both viruses and bacteria, and demonstrated that although infective exacerbations were associated with sputum purulence compared with those where no pathogen was detected, it found no difference in sputum purulence between exacerbations with viral or bacterial detection.…”
Section: From the Authormentioning
confidence: 99%
“…[44][45][46] Neutrophils are elevated in stable COPD compared to smokers and much more in exacerbations (sensitivity of 70% and specificity of 84%). 8,13,46 Neutrophil elastase growth (NE) and other antimicrobial peptides correlate with the severity of COPD exacerbations. Elevation of IL-6, IL-8 and TNF-alpha mediator levels correlate with persistent symptoms in exacerbation and their decrease announces the remission period.…”
Section: Sputum Biomarkers In Copdmentioning
confidence: 99%
“…11,13 Myeloperoxidase (MPO), TNF-alpha, IL-8 are associated with sputum purulence in bacterial exacerbations and high levels of WBC. 6,8 An increased number of eosinophils in the sputum can identify patients at risk for exacerbations, and patients with Asthma-COPD Overlap Syndrome (ACOS) who would benefit from early treatment with inhaled corticosteroids. 6,47,48 It is well-known that VEGF has a central role in vascular remodeling in COPD (with the appearance of pulmonary arterial hypertension).…”
Section: Sputum Biomarkers In Copdmentioning
confidence: 99%
See 1 more Smart Citation